2012
DOI: 10.1371/journal.pone.0041022
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure and Preserved Left Ventricular Function: Long Term Clinical Outcome

Abstract: BackgroundPatients with heart failure (HF) have a poor prognosis. The proportion of patients with HF and preserved left ventricular function (LVF) is increasing. Long term prognosis of HF with preserved LVF may not be so benign.ObjectivesTo evaluate the long term clinical outcome of patients with HF and preserved LVF and predictors of outcome.MethodsWe prospectively evaluated 309 patients hospitalized with a definite clinical diagnosis of HF. Patients were followed for a mean of 6.5 years for clinical outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…The comparison of patients with preserved and depressed LVEF confirmed slightly better prognosis of those with LVEF > 50% [22,23]. Although results of the multivariate Cox proportional hazard model performed for both groups of patients could be influenced by lower number of evaluated patients with preserved LVEF, conclusively we confirmed age > 70 years, creatinine level > 145 μmol/L and heart rate > 80 beats/min as parameters negatively affecting long-term survival.…”
Section: Predictors Of Long-term Mortalitysupporting
confidence: 58%
“…The comparison of patients with preserved and depressed LVEF confirmed slightly better prognosis of those with LVEF > 50% [22,23]. Although results of the multivariate Cox proportional hazard model performed for both groups of patients could be influenced by lower number of evaluated patients with preserved LVEF, conclusively we confirmed age > 70 years, creatinine level > 145 μmol/L and heart rate > 80 beats/min as parameters negatively affecting long-term survival.…”
Section: Predictors Of Long-term Mortalitysupporting
confidence: 58%
“…[23][24][25][26][27][28][29][30] The additional protocol inclusion criterion in TOPCAT of either a prior hospitalization in which heart failure was a prominent feature or an elevated natriuretic peptide level was intended to both improve diagnostic certainty and to augment risk. The assumption that those with a prior hospitalization would have higher risk [31][32][33][34][35] was confirmed only for the patients randomized from the Americas, suggesting that the nonadjudicated qualifying hospitalization criterion enrolled different patient populations. However, multifold lower event rates were also observed in the patients qualifying by natriuretic peptides from Russia/Georgia.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,15,16,17,18,19,20,21,22,23,24,25 Some studies have shown heart failure patients face a similar magnitude of risk regardless of ejection fraction 13,14,19 , while others have demonstrated lower event rates in patients with HFpEF compared to HFrEF. 16,17,18,22,23,24 This disparate finding regarding the effect of ejection fraction on event rates is also seen when the studies are grouped into acute heart failure, 13,14,15,16,17 versus chronic, prevalent heart failure.…”
Section: Discussionmentioning
confidence: 99%